Role of Immunological Method of Fecal Occult Blood Test for Screening Colorectal Diseases (Bangabandhu Sheikh Mujib Medical University Journal, 2011)
Background: Colorectal diseases specially colorectal carcinoma is one of the major health problems throughout the world. Therefore, early diagnosis of these diseases is mandatory. There are various screening methods are used for early diagnosis of colorectal diseases. Among them fecal occult blood test is the most widely used screening test. Objectives: The objectives of the present study were to find out the role of immunological method of fecal occult blood test for screening colorectal diseases. Methods: This was a prospective study consisted of 110 patients suspected to have colorectal diseases of both sexes attending in Gastroenterology and Clinical Pathology department of Bangabandhu Sheikh Mujib Medical University. Stool samples of all the patients were examined by immunological method of fecal occult blood test and then advised for colonoscopy and histopathology for confirmatory diagnosis. The results of immunological method of fecal occult blood test and the colonoscopic findings were compared. Results. Of 110 patients, 87 (79%) cases were positive and 23 (20.9%)cases were negative by immunological method of fecal occult blood test. According to colonoscopy and histopathology, 65(32.5%) cases were found to have colorectal diseases and 45(22.5%) cases had no pathology. Diseases detected by colonoscopy in occult blood test positive patients, 18(16.4%) colorectal polyp, 24(21.8%) colonic ulcer, 8(7.3%) colorectal cancer, 5(3.5%) inflammatory bowel disease, 7(6.4%) haemorrhoids and fissure, 2(1.8%) colonic diverticulum and 1(0.9%) proctitis. Among the 65(32.5%) lesions detected by colonoscopy,62(95.3%) cases were positive by immunological method of fecal occult blood test where as only three(3) lesions were found in occult blood test negative cases. The sensitivity, specificity, PPV and NPV of immunological method of fecal occult blood test (IFOBT) for detection of occult bleeding were 95.4%, 44.4%, 71.3% and 87.0% respectively. Conclusion: It can apparently be concluded from this study that the role of immunological method of fecal occult blood test for colorectal diseases is promising in Bangladesh. Key words: Colorectal diseases; Fecal occult blood test; Immunological method DOI: http://dx.doi.org/10.3329/bsmmuj.v4i2.8634 BSMMU J 2011; 4(2):76-80